Bodywork as systemic and inter-enactive competence: participatory process management in Feldenkrais® Method and Zen Shiatsu - Kimmel, Michael; Irran, Christine; Luger, Martin A. (Frontiers in Psychology, 2015)
Our micro-ethnographic study demonstrates how bodywork skills in Feldenkrais and Shiatsu are infused with systemic sensitivities. A micro-genetic study both of process vignettes and bodyworkers’ subjective theories reveals their intrinsically systemic self-awareness for process management – which is why we deem dynamic systems concepts a suitable meta-language. From an abstract angle, bodyworkers stimulate self-organization and dynamic homeostatic balance in the client’s somato-personal system. Operating in such a framework requires a progressive reconfiguring of the client’s attractor landscape, his or her systemic dispositions. Specifically, we argue that bodyworkers “context-intelligently” soft-assemble (frequently non-linear) synergies within their apperception of functional architectures of somato-systemic order. The client’s system is stimulated with a mix of perturbing and stabilizing interventions, while oscillating between eigenfunctions of joints, muscles, etc., and their integration in functional ensembles. In concrete embodied interaction this is implemented with continuous tactile coupling in a safe dyadic sphere and in an irreducibly real-time dynamics, even when sketchily planned. By sensorially charting systemic states in the making practitioners continuously stay apace of emergence, respond to minute changes, and customize reactions in a zone of proximal development (dynamic immediacy). Immediate responsiveness, in turn, benefits the client’s somatic learning. Finally, we inventorize the bodyworker’s tool-box at the operative level. Here a host of micro-enactive skills provides the necessary wherewithal for situated intervention, ranging from “educated senses” which know how to – often subtly – elicit information, via hands-on techniques from the action repertoire (grips, stretches, etc.), to habitus (proper posture, muscle activation, gaze patterns, etc.).